2016
DOI: 10.1111/cas.12933
|View full text |Cite
|
Sign up to set email alerts
|

Novel p53 target gene FUCA1 encodes a fucosidase and regulates growth and survival of cancer cells

Abstract: The tumor suppressor p53 functions by inducing the transcription of a collection of target genes. We previously attempted to identify p53 target genes by microarray expression and ChIP‐sequencing analyses. In this study, we describe a novel p53 target gene, FUCA1, which encodes a fucosidase. Although fucosidase, α‐l‐1 (FUCA1) has been reported to be a lysosomal protein, we detected it outside of lysosomes and observed that its activity is highest at physiological pH. As there is a reported association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 37 publications
5
41
0
Order By: Relevance
“…FUCA1 is induced by wild‐type p53 according to in vitro studies, and the expression of FUCA1 is downregulated in cancers with mutant p53 . Because that particular mutant p53 has an extended protein half‐life, an intensified signal can be detected at high frequency in OSCC and severe dysplasia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FUCA1 is induced by wild‐type p53 according to in vitro studies, and the expression of FUCA1 is downregulated in cancers with mutant p53 . Because that particular mutant p53 has an extended protein half‐life, an intensified signal can be detected at high frequency in OSCC and severe dysplasia .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ezawa et al . reported that FUCA1 was induced by wild‐type p53 . Many OSCC cases have mutations in TP53 , and strong chromogenic reaction to p53 caused by an increased half‐life of mutant p53 is detected in OSCC at high frequency .…”
mentioning
confidence: 99%
“…Based on data from previous works, it seems that no previous evidence about a relationship between α‐L‐FUCA‐1 and SS have yet been described. While genetic expression of α‐L‐FUCA‐1 has been recently correlated with tumors which suggests an important role of this glycosidase in chronic inflammatory response, fucosidase activity is closely related to lysosomal function, and its importance in the onset and progression of inflammation and autoimmune diseases has earlier been reviewed …”
Section: Discussionmentioning
confidence: 99%
“…Based on data from previous works, it seems that no previous evidence about a relationship between α-L-FUCA-1 and SS have yet been described. While genetic expression of α-L-FUCA-1 has been recently correlated with tumors 27,28 which suggests an important role of this glycosidase in chronic inflammatory response, fucosidase activity is closely related to lysosomal function, and its importance in the onset and progression of inflammation and autoimmune diseases has earlier been reviewed. 29 Interestingly, in SS the chronic inflammatory state is exacerbated by lysosome function, which in animal models has been shown to Statistics were calculated in a triplicate experiment with a minimal size of 10-20 samples, according to methods described in the text.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few fucosidases from distinct eukaryotes have been described despite the ubiquity of fucosidases in Metazoa (Intra, Perotti, Pavesi, & Horner, 2007) and the involvement of -L-fucosidases in many physiological processes (Ezawa et al, 2016;Goi et al, 1986Goi et al, , 1999.…”
mentioning
confidence: 99%